The Long Tail, Copyright and Libraries - Van Borm, Julien (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
This paper is about the Long Tail as defined by Chris Anderson in 2006, its direct implications for copyright and its possible consequences for libraries and heritage institutions, e.g. for document delivery and the creation of repositories with images, sound registrations and documents.